Caracterización fisicoquímica del bagazo de caña de azúcar (Saccharum officinarum) para uso en la alimentación animal - Sarmiento Gallegos, Saida Tatiana (2024)
The main objective of this research was to carry out the physicochemical characterization of sugar cane bagasse obtained in an industrial and artisanal way in the canton of Catamayo, Loja province. The investigation focused on determining the potential application of this bagasse as a component of animal feed. A completely randomized design was used. One-kilogram samples of sugarcane bagasse were collected from both the panelera (artisanal) and conventional sugarcane industry. The physical properties (water holding capacity, bulk density, and moisture) of the bagasse were determined. The chemical composition of the samples was evaluated on a dry basis, by bromatological analysis (pH, acidity, dry matter, ash, protein, and ethereal extract), and fiber analysis: crude fiber (CF), neutral detergent fiber (NDF), acid detergent fiber (ADF) and acid detergent lignin (ADL). Following data collection, all variables under investigation were statistically analyzed using the InfoStat software. A significant statistical difference was detected in all analyzed parameters except for acidity and ash. The results obtained indicated acceptable nutritional value for both bagasse samples. However, artisanal bagasse exhibited superior physical properties, chemical content (including dry matter, ash, crude protein and ethereal extract) and fiber content, suggesting that this by-product could be considered a viable alternative for animal feed, especially for ruminants.